2013
DOI: 10.1371/journal.pone.0053276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Virion-Incorporated Host Proteins Required for Herpes Simplex Virus Type 1 Infection through a RNA Interference Screen

Abstract: Viruses are strictly dependent on cells to propagate and many incorporate host proteins in their viral particles, but the significance of this incorporation is poorly understood. Recently, we performed the first comprehensive characterization of the mature herpes simplex virus type 1 (HSV-1) in which up to 49 distinct cellular proteins were identified by mass spectrometry. In the present study, we sought to identify if these cellular factors are relevant for the HSV-1 life cycle. To this end, we performed a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 61 publications
4
53
0
Order By: Relevance
“…Furthermore, the GFP-tagged viral particles often, but not always, colocalized with DDX3X in the cytoplasm (Fig. 5B), in agreement with the incorporation of this cellular protein in mature virions (21). A time course revealed that DDX3X started to aggregate between 3 and 6 h postinfection (hpi) and that this intensified with time (Fig.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Furthermore, the GFP-tagged viral particles often, but not always, colocalized with DDX3X in the cytoplasm (Fig. 5B), in agreement with the incorporation of this cellular protein in mature virions (21). A time course revealed that DDX3X started to aggregate between 3 and 6 h postinfection (hpi) and that this intensified with time (Fig.…”
Section: Resultssupporting
confidence: 68%
“…This confirmed that DDX3X is indeed a modulator of the HSV-1 life cycle. It also ruled out that nonspecific off-target effects were responsible for our past findings (21).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…These proteins are known to be involved in the regulation of signal transduction pathways by modulating the activities of client proteins via interaction with phosphoserine or phosphothreonine. Interestingly, Stegen and colleagues recently showed in a small interfering RNA (siRNA) screen that one of the 14-3-3 family members, 14-3-3 zeta, contained in virions, significantly supported HSV-1 production in cell culture (62). It remains to be determined if 14-3-3 proteins also influence HCMV infection.…”
Section: Discussionmentioning
confidence: 99%